Perinatal autopsy in Ghana: Healthcare workers knowledge and attitude - Alim Swarray-Deen; Dzifa A. Attah; Promise E. Sefogah; Nana E. Oduro; Hanson G. Nuamah; Mercy A. Nuamah; Catherine Adzadi; Samuel A. Oppong (Frontiers Media S.A., 2022)
BackgroundPerinatal mortality refers to stillbirths and early neonatal deaths. Stillbirth, the death of a foetus from 28 weeks or with a birth weight 1,000 g or above, and early neonatal deaths, the death of a new-born within 24 h of delivery, are among the most distressing global health problems, with approximately 2 million stillbirths occurring annually. Although a post-mortem examination of the stillborn baby is essential for understanding and learning the cause of stillbirth, many couples decline the procedure. Sub-Saharan Africa has one of the highest stillbirth rates in the world, yet there is a dearth of studies on post-mortem uptake from the region.AimTo explore healthcare professionals' views and perceptions of perinatal autopsy in Ghana.MethodsMixed-method approach consisted of semi-structured interviews and an electronic cross-sectional survey to evaluate the views and perceptions of healthcare professionals at Korle-Bu Teaching Hospital on autopsy for stillbirths and early neonatal deaths. Descriptive quantitative data were summarised in frequencies and percentages, and statistical results and descriptions were tabulated and coded in terms of types of barriers. For the qualitative aspect, the audio-taped interviews were transcribed, themes generated, and direct quotes and descriptions were coded for all knowledge, beliefs, attitudes and practices concerning the barriers and facilitators for post-mortem.ResultsNinety-nine healthcare professionals participated. No participant had formal training regarding counselling for perinatal autopsy and 40% had "no idea" who is responsible for counselling and obtaining consent for a perinatal autopsy. Forty-four percent (44%) of the participants knew of only the "Conventional/ Full" autopsy and <4% were aware of less invasive methods of performing an autopsy. Qualitative data showed healthcare worker influence, religious and financial considerations impede the implementation of perinatal autopsies. Despite the low uptake of perinatal autopsies, interviews from healthcare workers suggest acceptance rates would improve if parents knew about different options, especially less invasive procedures.ConclusionAt Ghana's largest referral centre, perinatal autopsy counselling and uptake are at extremely low levels. Most healthcare professionals have little knowledge, skills, and capacity to advise parents regarding perinatal autopsies. Training is needed to update the workforce on recommended perinatal autopsy practices.